The Influence of Principal's Authentic Leadership and Work Climate on Teachers' Social Competence at SMKN 1 Kuantan Mudik - Darmayanti, Suci; Bunari , Bunari; Isjoni , Isjoni (Journal Corner of Education, Linguistics, and Literature, 2024)
This study aims to determine the influence of (1) the principal’s authentic leadership and (2) the work climate on (3) teachers’ social competence at SMKN 1 Kuantan Mudik. This research adopts a quantitative approach with a random sampling technique, meaning the samples are selected randomly. The data collection method used in this study is a questionnaire. The results indicate an influence of teachers' social competence on teachers' social competence. The partial hypothesis test shows a significance value of 3.507. By comparing the calculated t-value and the t-table value (3.507 > 1.671), the hypothesis is accepted. The conclusion is that since the calculated t-value (3.507) is greater than the t-table value (1.671) and the significance level is less than 0.05 (0.001 < 0.05), it means that ????a is accepted, and ????0 is rejected. This implies that, partially, there is a significant influence of the principal’s authentic leadership on teachers’ social competence at SMKN 1 Kuantan Mudik. Furthermore, there is also an influence of the work climate on teachers’ social competence. The partial hypothesis test results show a significance value of 4.039. By comparing the calculated t-value and the t-table value (4.039 > 1.671) and noting that the significance level is less than 0.05 (0.000 < 0.05), it means that ????a is accepted, and ????0 is rejected. This indicates that, partially, there is a significant influence of the work climate on teachers’ social competence. The combined influence of the principal’s authentic leadership and the work climate is measured at (3.150), as the calculated F-value (33.690) is greater than (3.150), and the significance level (0.000) is less than 0.05. Therefore, ????0 is rejected, and ????a is accepted. This demonstrates a significant influence of the principal’s authentic leadership and the work climate on teachers’ social competence at SMKN 1 Kuantan Mudik.